Compiling Hilbert's Ïµ Operator - Leino, Rustan (LPAR-20. 20th International Conferences on Logic for Programming, Artificial Intelligence and Reasoning - Short Presentations, 2015)
Hilbert’s epsilon (ϵ) operator is a binder that picks an arbitrary element from a nonempty set. The operator is typically used in logics and proof engines. This paper contributes a discussion of considerations in supporting this operator in a programming language. More specifically, the paper presents the design choices made around supporting this operator in the verification-aware language Dafny.